Small molecules as activators in medicinal chemistry (2000–2016). (3rd October 2017) - Hameed, Abdul; Al-Rashida, Mariya; Alharthy, Rima D.; Uroos, Maliha; Mughal, Ehsan Ullah; Ali, Syed Abid; Khan, Khalid Mohammed
ABSTRACT: Introduction : From therapeutic point of view, it is often beneficial to enhance the expression of certain enzymes whose low expression is responsible for the observed ailment. Small molecules as activators of several enzymes have great biological potential as anti-microbial and anti-cancer agents, for the treatment of diabetes, obesity, metabolic disorders, and for the treatment of neurological disorders including Alzheimer's disease. This review covers patents describing small molecules as activators, and provides structural leads for the design of even more potent activators. Area covered : This review is focused on small molecules that have been explored as activators of enzymes in the last and current decade (2000–2016). Expert opinion : The ability to modulate activity of enzymes has long been a quest of medicinal chemistry. This has been the impetus behind the development of a plethora of drugs as enzyme inhibitors. However only a few enzyme activators as drugs have made it to the market. Disorders characterized by supressed enzyme activity can be treated by enhancing the activity of a specific enzyme.